ANALYSIS OF RESTAURANT-ASSOCIATED FOODBORNE ILLNESS COMPLAINTS IN KANSAS, 2009-2012 - Liu, Yang (My University, 2013)
Foodborne illness is a common but in many calls preventable disease. The Centers for Disease Control and Prevention has reported over half of the foodborne illness outbreaks were associated with restaurants. In Kansas, the state and local health departments are responsible for investigation of foodborne illnesses. The Kansas Department of Health and Environment and Kansas Department of Agriculture work together to monitor the restaurant-based intrastate foodborne illnesses. Restaurant-based foodborne illness complaint data from 2009 to 2012 were analyzed for this study. The objective was to compare characteristics of these complaints and to evaluate what information regarding the complaint would more likely lead to a foodborne illness outbreak. Of the 1,011 complaints, 109 were investigated, and 46 were confirmed as outbreaks. The investigation rate of all complaints was 10.8%, and the outbreak rate of all the investigation was 42.2%. Etiology of these outbreaks indicated two major pathogens: 30.4% of Norovirus, and 8.7% Salmonella spp. More complaints and outbreaks were seen in areas with higher populations. Outbreak confirmation was more frequent among complaints involving multiple households, and more brief exposure-to-illness time.
Keywords: Public health; Food borne illness; Salmonella spp; Norovirus; Public Health (0573)